RADIOTHERAPY-INDUCED CHANGES IN ORAL CAVITY BETA-DEFENSIN LEVELS IN HEAD AND NECK CANCER PATIENTS - Suomi, Emma (My University, 2025)
Background: Beta-defensins (hBDs) are small cationic peptides that have broad-range of antimicrobial activity and take part in tissue modulation. Secretion characteristics of hBDs may differ in various cancer types and it may be also affected by radiotherapy treatment affecting the mucosa. The present study aimed to investigate the oral cavity hBD 1-3 levels in head and neck cancer patients and its relation to radiotherapy treatment. Materials and Methods: Sixteen patients (all with a history of smoking) were included in this study. Periodontal parameters were measured before radiotherapy and medical information were collected from registries. Oral rinses of patients collected before radiotherapy,1st ,3rd ,6th weeks of radiotherapy treatment and 1st month following the end of radiotherapy. hBD 1-3 levels were measured using ELISA. Results: Losses were observed in all hBD values (hBD-1 29%, hBD-2 29%, and hBD-3 76%). In comparison to the pre-treatment, increased hBD-1 levels were observed during radiotherapy at week 6 (p=0.019). hBD-1 levels return back to pretreatment levels after the finalization of radiotherapy. No significant change was detected for hBD-2 or hBD-3 levels during or after radiotherapy. Conclusions: The loss of beta defensins in patients with head and neck cancer may indicate a higher likelihood of developing periodontal and other mucosal diseases. Additionally, radiotherapy may raise hBD-1 levels in the oral cavity of these patients. The constant expression of hBD-1, which is distinct from the infection and inflammation-dependent expression profiles of hBD-2 and hBD-3, may explain why this peptide is the only one affected by radiotherapy.
Keywords: pään- ja kaulan alueen syöpä, sädehoito, beta-defensiini